Visual nudging of navigation strategies improves frequency discrimination during auditory-guided locomotion - Malzacher, Annalenia; Hilbig, Tobias; Pecka, Michael; Ferreiro, Dardo N. (Frontiers in Neuroscience, 2025)
Perception in natural environments requires integrating multisensory inputs while navigating our surroundings. During locomotion, sensory cues such as vision and audition change coherently, providing crucial environmental information. This integration may affect perceptual thresholds due to sensory interference. Vision often dominates in multimodal contexts, overshadowing auditory information and potentially degrading audition. While traditional laboratory experiments offer controlled insights into sensory integration, they often fail to replicate the dynamic, multisensory interactions of real-world behavior. We used a naturalistic paradigm in which participants navigate an arena searching for a target guided by position-dependent auditory cues. Previous findings showed that frequency discrimination thresholds during self-motion matched those in stationary paradigms, even though participants often relied on visually dominated navigation instead of auditory feedback. This suggested that vision might affect auditory perceptual thresholds in naturalistic settings. Here, we manipulated visual input to examine its effect on frequency discrimination and search strategy selection. By degrading visual input, we nudged participants’ attention toward audition, leveraging subtle sensory adjustments to promote adaptive use of auditory cues without restricting their freedom of choice. Thus, this approach explores how attentional shifts influence multisensory integration during self-motion. Our results show that frequency discrimination thresholds improved by restricting visual input, suggesting that reducing visual interference can increase auditory sensitivity. This is consistent with adaptive behavioral theories, suggesting that individuals can dynamically adjust their perceptual strategies to leverage the most reliable sensory inputs. These findings contribute to a better understanding of multisensory integration, highlighting the flexibility of sensory systems in complex environments.